InAs/GaAs quantum dots on germanium-on-insulator-on-silicon substrates (GeOI) using molecular beam epitaxy - Fitzgerald, Eugene A. (2013)
InAs/GaAs quantum dots (QDs) on GeOI were grown at various growth temperatures and in-depth photoluminescence study was conducted to characterize the optical properties of QDs on GeOI. InAs QDs with room temperature emission of 1.26 μm and areal density of 4.8 × 1010 cm-2 were obtained. It was shown that high QD growth temperature helps to promote uniform dot size distribution but In-Ga intermixing may lead to excessive thermal escape of carriers. Photoluminescence studies suggest that QDs on GeOI have good optical quality but with small amount of defects, acting as non-radiative recombination centers.